2005
DOI: 10.1071/ch04289
|View full text |Cite
|
Sign up to set email alerts
|

The Mediated Electrodeposition of Polypyrrole on Aluminium Alloy

Abstract: The direct electrodeposition of conjugated polymers onto active metals such as aluminium and its alloys is complicated by the concomitant oxidation of the metal that occurs at the positive potential required for polymer formation/deposition. We have developed an approach that uses electron transfer mediation to reduce the deposition potential of polypyrrole on aluminium and aluminium alloy by nearly 500 mV, permitting film deposition from aqueous solution with nearly 100% current efficiency. The mediator used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 18 publications
1
23
0
Order By: Relevance
“…ICPs performance is greatly affected (Levine et al, 2005a) and understanding properties of oxide formed in ETM presence is necessary for successful ICPs deposition. The ETM influence of PPy deposition on Al alloy surface was described by Levine et al (2005b). The ETM influence on Al oxide formation is reported in current paper.…”
Section: Introductionmentioning
confidence: 93%
“…ICPs performance is greatly affected (Levine et al, 2005a) and understanding properties of oxide formed in ETM presence is necessary for successful ICPs deposition. The ETM influence of PPy deposition on Al alloy surface was described by Levine et al (2005b). The ETM influence on Al oxide formation is reported in current paper.…”
Section: Introductionmentioning
confidence: 93%
“…5 and shows a somewhat rougher surface than that obtained by mediated electrodeposition from aqueous solution. 18 Interestingly, the conductivity image reveals a rather uniform conductivity across the surface, the current averaging ca. 0.5 nA across the surface for a 50 mV bias potential.…”
Section: Conductivity Of the Ppy/tfsi Filmmentioning
confidence: 98%
“…[15][16][17] The mediator used most often in this earlier work was the disodium salt of 4,5-dihydroxy-1,3-benzenedisulfonate (DHDBS, also known as Tiron Ò ), which also served as the dopant or counter ion in the polymer, but other mediators appear promising and a mechanism has been proposed. 18 Galvanostatic electrodeposition of PPy in the presence of DHBDS leads to uniform, adherent, conducting, electroactive films. 15 Electrochemical atomic force microscopy studies 19 in combination with the potential-time curves obtained during galvanostatic electrodeposition of PPy 15 indicated that DHBDS mediates both the initial nucleation event (initial PPy deposition on the Al/Al 2 O 3 surface) and the film growth stage (PPy deposition on PPy).…”
Section: Introductionmentioning
confidence: 99%
“…We attribute this behavior to the electroactive dopant BDA (Tiron) which appears to play a role in the mechanism of O 2 reduction at the PPy-BDA film. We have previously described the ability of BDA to mediate the electrodeposition of PPy on AA [22][23][24][25].…”
Section: Polarization Characteristics Of Ppy Film and Aa 2024-t3mentioning
confidence: 99%